PENEGAKAN HUKUM TERHADAP DEMONSTRAN YANG BERTINDAK ANARKIS BERDASARKAN UNDANG – UNDANG NOMOR 9 TAHUN 1998 TENTANG KEMERDEKAAN MENYAMPAIKAN PENDAPAT DI MUKA UMUM (STUDI KASUS DEMONSTRASI MAHASISWA DI PEKANBARU) - Fredrick Constanthia Thianda; Mukhlis R; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
In Article 28 of the 1945 Constitution of the Republic of Indonesia states that everyone is free to associate, gather and express opinions orally and in writing in public. As for the forms of conveying an agreement in public, namely by way of demonstrations or associations, parades, general meetings and free forums. Then the procedures for submitting the agreement in public are regulated in the Regulation of the Head of the State Police of the Republic of Indonesia Number 7 of 2012 concerning Procedures for Providing Services, Safeguarding and Handling Cases for Submitting Opinions in Public. Lately we have seen that many people, especially students in Pekanbaru, in conveying their statements in public often end up in chaos or anarchism and clash with the Police. So that researchers need to research related to how law enforcement against demonstrations or actions carried out by students in Pkanbaru which ended in chaos or anarchism at the Pekanbaru City Police. This type of research is sociological legal research, namely research that seeks a correlation between law and society. This research is descriptive in nature, namely the researcher tries to provide a description of the case being studied. In this study using qualitative data analysis which means explainnning and concluding about the data that has been collected by the author. This research uses codified primary and secondary data. The result of this research is that law enforcement against demonstrators with an anarchic attitude that occurred in the city of Pekanbaru has never or has not been brought forward to the stage of investigation and investigation by the Police. This happened because in the case of law enforcement against anarchist demonstrators, there must first be a report to the Police that a person or a representative from this Government agency has suffered losses due to demonstrations that have been conducted by students. However, law enforcement against these demonstrators can also be carried out without any report from the injured party if in the demonstration there are protesters caught in the hands of being caught carrying sharp weapons, carrying out theft and committing vandalism. Keywords: Student – Demonstration - Anarchist